Getting started with Python and Raspberry Pi : learn to design and implement reliable Python applications on Raspberry Pi, using a range of external libraries, the Raspberry Pi's GPIO port, and the camera module /: learn to design and implement reliable Python applications on Raspberry Pi, using a range of external libraries, the Raspberry Pi's GPIO port, and the camera module. (2015) - Nixon, Dan
No abstract available